2022
DOI: 10.7717/peerj.13570
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome sequences of six Dalbergia species and its comparative analysis in the subfamily of Papilionoideae (Fabaceae)

Abstract: Dalbergia spp. are numerous and widely distributed in pantropical areas in Asia, Africa and America, and most of the species have important economic and ecological value as precious timber. In this study, we determined and characterized six complete chloroplast genomes of Dalbergia species (Dalbergia obtusifolia, D. hupeana, D. mimosoides, D. sissoo, D. hancei, D. balansae), which displayed the typical quadripartite structure of angiosperms. The sizes of the genomes ranged from 155,698 bp (D. hancei) to 156,41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Hence, positive selection in this gene may help explain the radiation of Ficus into diverse ecological niches. The rbcL gene, which is a photosynthesis-related gene encoding the large subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO), is commonly under positive selection in terrestrial plants but not in algae ( Kapralov and Filatov, 2007 ; Li et al, 2022 ), possibly due to more unstable thermal regimes on land ( Kapralov and Filatov, 2007 ). For example, rbcL is under positive selection in shade-tolerant Oryza species, probably in response to adaptive evolution associated with sunlight and thermal conditions ( Gao et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, positive selection in this gene may help explain the radiation of Ficus into diverse ecological niches. The rbcL gene, which is a photosynthesis-related gene encoding the large subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO), is commonly under positive selection in terrestrial plants but not in algae ( Kapralov and Filatov, 2007 ; Li et al, 2022 ), possibly due to more unstable thermal regimes on land ( Kapralov and Filatov, 2007 ). For example, rbcL is under positive selection in shade-tolerant Oryza species, probably in response to adaptive evolution associated with sunlight and thermal conditions ( Gao et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…During our analysis were subjected to positive selection of 12 plastid genes ( rpoB, ycf1, psaA, psaM, psbH, psbD, rbcL, ndhF, matK, accD, rps18 and ycf2 ), indicating that they may have contributed to environmental adaptation in Equisetum . Remarkably, the photosynthesis-related gene rbcL encoding the RuBisco’s large subunit, which displayed particularly pronounced indications, is commonly under positive selection in terrestrial plants but not in water plant ( Li et al., 2022 ), possibly due to more unstable thermal regimes on land ( Kapralov and Filatov, 2007 ). In this study, we collected Equisetum from habitats with diverse sunlight exposure, and thus rbcL may be probably in response to adaptive evolution associated with sunlight and thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, ycf1 encodes unknown proteins and is competent in identification at genus and species level of orchids [ 46 ]. Recent studies have revealed that these eight genes with positive selection in flowering plants are common [ 27 31 , 33 , 35 , 47 , 48 ]. For example, ndhF has been reported as a positive selection in the Aroideae species [ 30 ]; clpP and ycf1 have been reported as positive selections in the Polystachya species [ 31 ]; ndhA and clpP have been reported as positive selections in the Hoya species [ 35 ]; ndhA , clpP , rps12 and ycf1 have been reported as positive selections in the Zingiber species [ 33 , 47 ]; and cemA , clpP , ndhF , petB , rps12 and ycf1 have been reported as positive selections in the Dalbergia species [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that these eight genes with positive selection in flowering plants are common [ 27 31 , 33 , 35 , 47 , 48 ]. For example, ndhF has been reported as a positive selection in the Aroideae species [ 30 ]; clpP and ycf1 have been reported as positive selections in the Polystachya species [ 31 ]; ndhA and clpP have been reported as positive selections in the Hoya species [ 35 ]; ndhA , clpP , rps12 and ycf1 have been reported as positive selections in the Zingiber species [ 33 , 47 ]; and cemA , clpP , ndhF , petB , rps12 and ycf1 have been reported as positive selections in the Dalbergia species [ 48 ]. Among the analyzed species of Costaceae, they possessed diversity of ecological habitats, such as shade under the woods, forest margins, moist places in valleys, roadsides and ditch sides [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%